List of Birds Sigthed on Livestock Farms in Sucre, Colombia (Global Journal of Science Frontier Research, 2020)
The rural areas of the Department of Sucre, Colombia, have a considerable bird species richness, but there are not many reports on this. In this work, we classify and record the species we sighted in nine cattle farms in the region. We obtained information on the relative abundance of each species (frequency of observation about the total sample), and biotopes where we observe them. We use chi square to know if there was an association between these parameters and also about to the food guild to which the species belong. We obtained the latter in the specialized bibliography. We use the Sorensen Index, to determine the degree of similarity of the communities of species in each biotope. We spot 103 species of birds. The best-represented order was Passeriformes, with eleven families and 36 species. Most of the species were abundant, and the biotope with the highest sighting was the open area, although many species were present in more than one biotope. We found no association between the abundance of species and the biotope in which we observed them, nor about the food guild. Among the species sighted, 21 are migratory, mostly wintering with permanent breeding populations. In this paper we discuss the importance of livestock farms for wildlife conservation.
Keywords: birds; species richness; livestock farms; relative abundance